An unusual case of an elderly patient with multifocal pyomyositis - Vashishtha, Vishesh; Kulkarni, S. V.; Srivastava, V. L.; Saxena, Sagar (International Surgery Journal, 2025)
Pyomyositis is an uncommon infection of the skeletal muscle that typically results in the formation of an abscess. We report an unusual case of a 74-year-old lady who presented with impaired mobility for 04 months, bilateral diffuse lower limb swelling without other signs of inflammation and normal leucocyte count, which emerged as methicillin-resistant Staphylococcus aureus (MRSA) pyomyositis involving different compartments of both lower extremities and responded promptly with timely surgical intervention. The role of high index of suspicion, sequential multimodal imaging in assessing infectious musculoskeletal pathologies and prompt timely operative intervention for source control remains pivotal.